2017
DOI: 10.1002/jor.23478
|View full text |Cite
|
Sign up to set email alerts
|

Radiolucency in stemless shoulder arthroplasty is associated with an imaging phenomenon

Abstract: Stemless humeral implants show comparable midterm clinical results compared to stemmed components. Recently, radiolucencies around the metaphyseal seating of humeral stemless implants were reported on postoperative radiographs. It is controversial whether they are attributable to bone resorption. We hypothesized these radiolucencies result from imaging artifacts. Seven cadaveric specimens (three male and four female) were first radiographed and then scanned with CT. A stemless humeral component of current desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In this context, it should be mentioned that radiographic changes around humeral components are to be interpreted with caution. Hudek et al showed that, depending on the radiation scatter, radiolucency in stemless shoulder arthroplasty is associated with an imaging phenomenon with a high rate of misinterpretation [12].…”
Section: » Reduced Stem Lengths Closely Mimic the Intact Shoulder Statementioning
confidence: 99%
“…In this context, it should be mentioned that radiographic changes around humeral components are to be interpreted with caution. Hudek et al showed that, depending on the radiation scatter, radiolucency in stemless shoulder arthroplasty is associated with an imaging phenomenon with a high rate of misinterpretation [12].…”
Section: » Reduced Stem Lengths Closely Mimic the Intact Shoulder Statementioning
confidence: 99%
“…After switching to an impaction method there might be a learning curve for the surgeon which can lead to difference in result. Furthermore, the method of examining radiolucent lines commonly used as indication for loosening seems to have limitations of its own [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of stress shielding under a stemless implant is unknown and could possibly be explained by a radiographic phenomenon rather than actual bone loss. 14,20,24,40 We did not include evaluation of axillary radiographs in this study as the majority were performed at one of several outside community radiology clinics and inconsistency in arm positioning did not allow for reliable grading with this method. This also limited our ability to evaluate ''recentering'' the glenohumeral joint.…”
Section: Discussionmentioning
confidence: 99%